Effect of Education on Knowledge and Attitude Level Related to Vitamin D in Pharmacy Students - Amelia Lorensia; Rifaatul Laila Mahmudah; Matina Naim; Dian Natasya Raharjo (Journal of Tropical Pharmacy and Chemistry, 2023)
Indonesia is a country located in the tropics with sun exposure throughout the season. Sun exposure is the best source of vitamin D and there have been no cases of vitamin D intoxication due to excessive sun exposure. Pharmacy students tend to lack knowledge of vitamin D. Changes in lifestyle and modernization lead to high use of sunscreens which can lead to a decrease in the synthesis of vitamin D in the skin. This research was conducted to determine the differences in knowledge and attitudes towards sun exposure using cross sectional method on 100 first semester pharmacy students and 100 final semester students. Test differences in aspects of knowledge and attitudes using odds ratios. The results of the knowledge aspect odds ratio test are 1,000 and the attitude aspect odds ratio test results were 0.583 so that it can be concluded that both knowledge and attitudes towards sun exposure have the same risk tendency for first semester and final semester pharmacy students.